Joint application of fungicide and rhizobacteria on tomato seeds - Magalhães Madureira , Lidiane; Cássia Ferreira Ribeiro , Regina; Márcia Santos de Souza David, Andréia; Aparecida Xavier , Adelica; Victor Magalhães Pacheco , Paulo; Dener da Silva, Cleisson; Vinícius de Souza Cangussú, Lucas; Cantuária Figueiredo, Josiane (Comunicata Scientiae, 2022)
Tomato (Lycopersicon esculentum) is a vegetable that stands out among the others for being one of the most consumed and industrialized. Among the technologies for increasing crop productivity, the treatment of seeds with fungicides and or rhizobacteria that promotes plant growth stands out. The objective of the work was to evaluate the effect of the combined application of fungicide and rhizobacteria on the germination and vigor of tomato seeds. The assays were mounted in DIC in a factorial scheme 10 x 2 + 1 (10 rhizobacteria, with or without fungicide and additional treatment: fungicide only), with four replications. The following characteristics were evaluated: water content, germination, first germination count, germination speed index (IVG), seedling emergence and accelerated aging. In general, the treatment of seeds with rhizobacteria stimulates the physiological quality of tomato seeds. The rhizobacteria Paenibacillus lentimorbus-69 and Bacillus subtilis-34 proved to be compatible with the fungicide, favoring the germination and vigor of the seeds in relation to the treatment with fungicide